2000
DOI: 10.1111/j.1741-3729.2000.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult Adoptees and Their Friends: Current Functioning and Psychosocial Well‐Being*

Abstract: Adoptees (n ϭ 100) and a matched group of their friends completed measures of psychosocial well-being thought particularly salient for adult adoptees. Results indicated more similarities (life satisfaction, life regrets, purpose in life, intimacy, substance abuse) than differences (connectedness, depression, self-esteem) between the two groups. Adoptees expressed stronger regrets about 75 general than adopted-related issues. Follow-up analyses suggested greater variability within the adoptee than the friend gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 34 publications
4
70
0
Order By: Relevance
“…Originally, we set out to test assumptions that Five Phases of Adoption Issues adult adoptees exhibit greater psychosocial dysfunction than do adults who were not adopted. We found (Borders et al, 2000) that, with a few exceptions, the middle-aged adoptees were more similar than different in comparison with a matched group of nonadopted friends. We also discovered, however, that there was significantly more variation among the adult adoptees than among their friends; whether or not the adoptees had searched for their biological parents helped to explain this greater variability.…”
mentioning
confidence: 60%
“…Originally, we set out to test assumptions that Five Phases of Adoption Issues adult adoptees exhibit greater psychosocial dysfunction than do adults who were not adopted. We found (Borders et al, 2000) that, with a few exceptions, the middle-aged adoptees were more similar than different in comparison with a matched group of nonadopted friends. We also discovered, however, that there was significantly more variation among the adult adoptees than among their friends; whether or not the adoptees had searched for their biological parents helped to explain this greater variability.…”
mentioning
confidence: 60%
“…Some studies compared adopted and non-adopted young adults, mainly focusing on mental health and psychological well-being; however, results of these studies are not consistent and have exhibited contradictory findings. On one hand, a number of studies demonstrated that adult adoptees are more likely to be at higher risk for psychopathological outcomes and lower level of psychological well-being (Cubito & Obremski Brandon, 2000;Cantor-Grace & Pedersen, 2007;Feeney, Passmore, & Peterson, 2007;Hjern, von Borczyskowski, Lindblad, & Vinnerljung, 2006;Levy-Shiff, 2001;Passmore, Fogarty, Bourke, & Baker-Evans, 2005;Tieman, van der Ende, & Verhulst, 2005), while other studies failed to find any differences in adjustment and in psychological wellbeing between adopted and non-adopted adults (Borders, Penny, & Portnoy, 2000;Feigelman, 2000;Irhammar & Bengtsson, 2004;Kelly, Towner-Thyrum, Rigby, & Martin, 1998;Smyer, Gatz, Simi, & Pedersen, 1998).…”
mentioning
confidence: 97%
“…Further, this study adds to a growing body of literature identifying differences between searchers and non-searchers (e.g., Borders et al, 2000). However, we also found differences among searchers, indicating that it was only those searching in order to resolve personal issues (e.g., personal problems or a need for belonging) who experienced higher depression and emotional arousability.…”
Section: Implications For Counselingmentioning
confidence: 44%
“…When researchers make distinctions among different types of adoptees, however, some adoptees seem more at risk for poor adjustment. Although Borders, Penny, and Portnoy (2000) found that adoptees had higher depression scores than their non-adopted friends, further analyses indicated that only 'searchers' (those who had searched for birth relatives) were more depressed than non-adoptees. Research also indicates that different groups of adoptees differ in their perceptions of their adoptive parents.…”
Section: Depression Emotional Arousability and Perceptions Of Parenmentioning
confidence: 99%